PENERAPAN EVIDENCE BASED NURSING (EBN) TERAPI STIMULASI ORAL UNTUK ATASI MASALAH REFLEKS HISAP LEMAH PADA BAYI BERAT LAHIR RENDAH (BBLR) - Clara Septi Amanda (2022)
LBW has poor coordination in sucking reflex causing malnutrition. This causes LBW to be able to increase the ability to eat through the mouth by strengthening the ability to suck, namely oral stimulation. Oral stimulation is defined as stroking or pressing on structures in and around the mouth. The purpose of this study was to analyze nursing care for LBW who have weak suction reflexes with oral stimulation. The respondents involved in this study amounted to two people with one of the babies given oral stimulation and nursing care. The intervention was carried out for 7 days with a frequency of once per day for 15 minutes. The measurement of the status was obtained from the early feeding skill instrument, oral feeding volume, breastfeeding time, drinking frequency, and calculation of fluid requirements. The results of the study on the seventh day showed an increase in the suction reflex in intervention respondents who previously had a weak suction reflex with a value of 0 to have a strong suction reflex with a value of 14. Oral stimulation is recommended by the author to LBW who have a weak suction reflex in order to improve the suction reflex and accelerate oral feeding.